Sharia Risk Analysis of the Ijarah Muntahiya Bit Tamlik (IMBT) Contract: Perspectives of DSN-MUI Fatwas, PSAK 107, and OJK Regulations - Fenti Indah Kusumorini; Nafis Irkhami (Universitas Muhammadiyah Jember, 2025)
This research aims to comprehensively identify and analyze the potential Sharia risks inherent in the implementation of the Ijarah Muntahiya Bit Tamlik (IMBT) contract within the practice of Islamic financial institutions in Indonesia. This study is highly relevant given the growing volume of IMBT financing, which demands stricter compliance risk mitigation to maintain public trust and the integrity of the Sharia financial system. Furthermore, this study examines the synchronization of the IMBT regulatory framework as set out in the National Sharia Council-Indonesian Ulema Council (DSN-MUI) Fatwa, Financial Accounting Standards Statement (PSAK) No. 107, and the Financial Services Authority (OJK) Regulations. The research method employed is Normative Legal Research, utilizing a statute approach and a conceptual approach. Primary data sources are derived from content analysis of key regulations: DSN-MUI Fatwa No. 09/DSN-MUI/IV/2000, PSAK 107, and relevant OJK regulations. The findings indicate that the primary Sharia risk in IMBT lies in the promise of ownership transfer (wa’d), which may lead to ambiguity (gharar) and legal risk if not executed separately from the lease contract. A disharmony of interpretation was found, especially between the accounting treatment of PSAK 107, which tends to be based on economic substance, and the formal Sharia requirements of DSN-MUI. A clear harmonization of interpretation and a unified operational guideline are needed to ensure the legal certainty and Sharia compliance of IMBT, particularly in the aspect of accounting recognition and treatment, which can influence Sharia risk.